IMPLEMENTASI PROGRAM KEGIATAN ORGANISASI KEMAHASISWAAN DALAM MENUMBUHKAN PERILAKU KEPEMIMPINAN MAHASISWA DI IAIN MADURA - Zaifur Rofiq; Nor Hasan (re-JIEM (Research Journal of Islamic Education Management), 2021)
Student organizations are forms and means of channeling ideas, creations and works that can support students. The results of the study show that: First; Each ORMAWA organizes RAKER, which will be programmed in its leadership period from short to long term, then the results of the mutually agreed upon RAKER are submitted in RAKERGAB, SENAT students hold RAKERGAB which is attended by all ORMAWA. The work plan program in the program does not deviate from the Bylaws, then the agreed upon results are carried out according to RAKERGAB. Supporting factors include: the existence of good service from the leadership to students to carry out their activities programs in improving student leadership behavior, the leadership provides opportunities for students to create and creativity as always willing and always accompany and provide direction and motivation to students. The inhibiting factors include: Limited land and facilities that are still inadequate, lack of places to carry out limited activities, and limited provision of stationery.